2012
DOI: 10.3109/11038128.2012.700729
|View full text |Cite
|
Sign up to set email alerts
|

Children with myelomeningocele and independence in the toilet activity: A pilot study

Abstract: In this pilot study mutual goal setting in a step-by-step training programme based on professional observation of the toilet activity at home showed a better outcome than traditionally performed training in a hospital setting or with traditional habilitation support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Independence on the toilet affects quality of life, supporting efforts to enhance independence. Active goal‐oriented efforts from all care providers are probably required, already from infancy .…”
Section: Discussionmentioning
confidence: 99%
“…Independence on the toilet affects quality of life, supporting efforts to enhance independence. Active goal‐oriented efforts from all care providers are probably required, already from infancy .…”
Section: Discussionmentioning
confidence: 99%
“…For the SB group, a few studies have been published about different intervention methods aiming to enhance performance in everyday activities. One study [21] showed promising results in adults for goal management training, i.e., learning in a group setting how to use a strategy and another by Donlau et al [22] showed that a goal-focused approach helps children with SB to accomplish specific goals in self-care.…”
Section: Introductionmentioning
confidence: 99%
“…No interventions with conclusive evidence of effectiveness for improving self-care were identified. Constraint-induced movement therapy (Sakzewski et al 2014), goal-setting (Löwing et al 2009;Sorsdahl et al 2010;Donlau et al 2013;Hwang et al 2013), and powered mobility (Livingstone & Field 2014) were consistently promising interventions. Few papers explicitly stated proposed change mechanisms, but hypothesized mechanisms (described as 'barriers' and 'facilitators') emerged over the discussions with the young people and the adults (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…; Donlau et al . ; Hwang et al . ), and powered mobility (Livingstone & Field ) were consistently promising interventions.…”
Section: Resultsmentioning
confidence: 99%